FORMAÇÃO-EXPERIÊNCIA COMO UM CAMINHO DES-POSSÍVEL PARA TRADUTORES E INTÉRPETES DE LIBRAS-PORTUGUÊS - Oliveira, Cassio Pereira (2021)
In this dissertation, I propose an experiment to rethink the practices that constitute the education of Libras-Portuguese Translators and Interpreters (TILSP) based on the notion of experience matrix. The aim of this research is to understand how, in the historical process of constituting the education of Libras-Portuguese Translators and Interpreters, technologies for the modulation of their behaviors are established, as well as paths that are configured as escape routes. To contemplate and relate it in a theoretical-methodological experimentation, I produced three specific objectives, which are tangent through conversations with TILSP, they are: (i) To investigate the possibility conditions that contributed to the emergence of the education of Translators and Interpreters of Libras-Portuguese; (ii) To analyze how modulation technologies have been constituted in the behavior of Translators and Interpreters of Libras-Portuguese in their education process; and (iii) To problematize, based on conversations with the TILSP, how technologies are used in modulating behaviors related to a modern political rationality, as well as ways of being TILSP that are configured as escape routes. To operate analytically, I use governmentality and subjectivity as conceptual tools, which allowed me to observe how the educationexperience juxtaposition can operate doubly as an escape route that allows an attitude that goes beyond the limits established by the hegemonic discursive and non-discursive practices of modernity. I argue that the education of TILSP emerges from a rationality composed of practices ensured by disciplinary devices, organized life management and, memory modulation and its virtual powers. In this movement, I argue that the experience matrix modulates the paths in which we become TILSP and is correlated with neoliberal devices and subjectivation processes. Moreover, it is responsible for the emergence of four dominant subjective figures of the crisis, namely, the indebted, the mediatized, securitized and represented. Methodologically, I analyze these subjective figures as a result of the intersection of a series of pedagogical devices of production and mediation of the experience of oneself from a corpus of analysis produced through conversation as a procedure. In addition to the conversations, the analytical materiality is also composed of legal provisions and academic productions focused on the topic of TILSP education. Based on the data, I associate the subjective figures as an adjective element to the research subjects, such as (i) Indebted TILSP, (ii) Mediatized TILSP, (iii) Securitized TILSP and (iv) Represented TILSP. Thus, it is possible to develop the path of investigation, analysis and problematization of the practices by which we become TILSP. In this movement, education-experience is configured as a vector for thinking TILSP as subjects capable of subverting the processes that reproduce these figures of subjugation. Education-experience as a dis-possibility for TILSP, in addition to being situated in this flow of production of subjectivities, can be a way of revisiting our constitution as unnatural. The thesis that I defend in this work is that education-experience is an 7 attitude whose characteristic enhances ways of being TILSP through minor experiments existing in everyday life and inscribed in the here and now. Experiencing ways of constitution was a movement that, paradoxically to the scenario / context we live in (of deprivation of our human capacities, especially that of political action), we are facing an opportune time (kairós) where cooperation and productive interdependence are the conditions of the common. From the time, in the sense of kairós, we constitute ethical ways of existence that extend our degree of freedom. Therefore, the experience, in this sense, is taken as something that can and should be (re) thought, capable of separating us from ourselves and changing the way we think and act. In other words, education-experience is regarding life in its fullness of creation. The juxtaposition education-experience for TILSP can be constituted as a dis-possibility that goes beyond the established limits of constituted discursive and non-discursive practices of the ways of being TILSP.